THE LOST OEDIPAL STAGE OF HUMBERT HUMBERT IN NOBOKO'S LOLITA - Vicky Larasita Latifa Dinar; Nungki Heriyati (MAHADAYA: Jurnal Bahasa, Sastra, dan Budaya, 2021)
This paper analyses the lost oedipal stage of Humbert in Vladimir Nabokov’s Lolita. It aims to discover the main character’s motivation behind his sexual disorder and the inner conflicts of his psyche, in response to Humbert not experiencing the oedipal stage in his early years. The oedipal stage is a crucial development stage of a human being, and Humbert’s inexperience causes him to be unable to express his desires as an infant boy towards his mother resulting in his psyche developing abnormally. Humbert is considered a hebephiliac for his sexual attraction towards young girls due to the loss of maternal figure at the age of three. Thus, psychoanalysis theory by Sigmund Freud is used in order to analyse the impact of Humbert’s lost oedipal stage to his adult psyche by applying the tripartite theory. The data are collected using qualitative descriptive method, represented in direct quotes from the book. The paper reveals that Humbert’s lost oedipal stage holds a vital role in developing his sexuality in adult life. He only received a strong affection and love when he was thirteen, from Annabel that aged no older than fourteen. He has been holding on to the moment, in which he was able to express his desires as his id, and is unable to let it go even after Annabel’s decease, as his id was not fully fulfilled. This causes him a traumatic experience, leading to his sexual disorder which is developed further once he met Dolores Haze as Lolita.